Carborane: Dedicated to the Work of Professor Alan Welch (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue on carboranes is dedicated to Prof. Alan Welch on the occasion of his retirement and his outstanding contributions to the field of carborane chemistry. Polyhedral carboranes lie at the interface of organic and inorganic chemistry. One of their most attractive and important features is the variety and beauty of their chemical structures. They have found applications as diverse as catalysis, in Boron Neutron Capture Therapy, as liquid crystals and as semiconductors. This Special Issue illustrates the very comprehensive world of heteroborane chemistry, from liquid crystals to BNCT agents, di-halogen bonding to quantum chemical calculations of tetrel complexes of the carbonium ylide CB11H11, nickellacarboranes as potential acid–base sensors to revealing how the selective formations of metallacarborane diastereomers can arise and metallacarboranes as function as radical cation salts with dielectric or semiconductor properties.